SINERGI REKRUTMEN DAN SELEKSI KARYAWAN TRANSFORMASI KINERJA KARYAWAN PADA PT DUA BAROKAH SEJAHTERA TANGERANG SELATAN - Latif, Latif; Sunarto, Ading; Syarifudin Sukasih, Ahmad (Yayasan Education and Social Center, 2024)
To find out the influence of Employee Recruitment and Selection on Employee Performance at PT. Dua Barokah Sejahtera (D'Bro Chicken & Burger) Depok City. The method used is quantitative. The sampling technique used Saturated Sample and a sample of 60 respondents was obtained. To test and analyze the influence partially and simultaneously by using hypothesis tests (t-test and f-test). There is a significant influence between selection and employee performance. Results of Hypothesis Test (Test F) Simultaneous Recruitment (X1) and Selection (X2) on Employee Performance (Y) Based on the results of the study, the value of F calculated > F table or (31.621 > 3.16), this is also strengthened by a significance of < 0.050 or (0.000 < 0.050). Thus, H0 is rejected and H3 is accepted, which shows that there is a significant simultaneous influence between recruitment and selection on employee performance. The Hypothesis Test (t-test) of the Recruitment Variable (X1) on Employee Performance (Y) was obtained with a t-value calculated > t table or (7.999 >2.002). This is strengthened by a significance value of < 0.050 or (0.000 < 0.050). Thus, H0 is rejected and H1 is accepted, which shows that there is a significant influence between recruitment and employee performance. Results of the Hypothesis Test (Ujit) of Selection Variables (X2) on Employee Performance (Y) Based on the results of the study, the value of t calculated > t table or (4.374 > 2.002) This is also strengthened by a significance value of < 0.050 or (0.000 < 0.050).